Frozen Section Evaluation in Head and Neck Oncosurgery: An Initial Experience in a Tertiary Cancer Center - Sangeetha K NAYANAR; Aswathi KRISHNAN M; Mrudula K I; Sajith Babu THAVAROOL P; Shivakumar THIAGARAJAN (Federation of Turkish Pathology Societies, 2019)
Objective: Frozen section evaluation is routinely used by oncosurgeons across specialties for rapid assessment of the presence of tumor in any tissue and its most common use is in surgical margins. Today, the use of intraoperative frozen-section evaluation of surgical margins is an accepted and frequent practice in head and neck oncology. This study aims to determine the efficacy and accuracy of frozen sections in head and neck cancer patients and compare the results with the respective paraffin sections and also to analyze the reasons for any disparity between them. Material and Method: A retrospective study was conducted to evaluate efficacy and accuracy of frozen section in head and neck cancer of 265 patients, treated at a tertiary cancer centre hospital between January 2013 to December 2014. Results: Out of 265 cases, it was found that 12.6% of these sections showed true positivity, 6.3% false positivity, 2.9% false negativity and 78.2% true negativity. The study also shows a sensitivity of 82.05% and specificity of 96.46%. Conclusion: Our study shows that intraoperative frozen section reports are specific and highly sensitive. We recommend a minimum of 3-4 sections, optimum cryostat temperature, good section thickness and quality staining for a good concordance rate.